Dampak Economic Value Added, Market Value Added dan Good Corporate Governance Terhadap Nilai Perusahaan Melalui Mediasi Ukuran Perusahaan - Mario Randi Banusu; Henny A. Manafe; Yolinda Yanti Sonbay; Stanis Man (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
This research aims to analyze the influence of Economic Value Added (EVA), Market Value Added (MVA), Good Corporate Governance (GCG) on Company Value by Mediating Company Size in Food and Baverage Companies listed on the Indonesia Stock Exchange. The population in this study were 22 companies which were then used as samples. The analysis technique uses descriptive and inferential statistics. The research results show that EVA and MVA have a negative and significant effect on company value, GCG does not have a significant effect on company value and company size has a positive and significant effect on company value. Company size is able to mediate the influence of MVA and GCG on company value so that it has a positive and significant effect, but it is not able to mediate the influence of EVA on company value.